Can Helicobacter pylori infection influence human reproduction? - Moretti, Elena (Baishideng Publishing Group Inc, 2014)
Helicobacter pylori (H. pylori) infection could be associated with extra-digestive diseases. Here, we report the evidences concerning the decrease in reproductive potential occurring in individuals infected by H. pylori, especially by strains expressing CagA. This infection is more prevalent in individuals with fertility disorders. Infected women have anti-H. pylori antibodies in cervical mucus and follicular fluid that may decrease sperm motility and cross react immunologically with spermatozoa, conceivably hampering the oocyte/sperm fusion. Infection by CagA positive organisms enhances the risk of preeclampsia, which is a main cause of foetus death. These findings are supported by the results of experimental infections of pregnant mice, which may cause reabsorption of a high number of foetuses and alter the balance between Th1 and Th2 cell response. Infected men have decreased sperm motility, viability and numbers of normally shaped sperm and augmented systemic levels of inflammatory cytokines, such as tumor necrosis factor-α, which may damage spermatozoa. In countries where parasitic infestation is endemic, detrimental effects of infection upon spermatozoa may not occur, because the immune response to parasites could determine a switch from a predominant Th1 type to Th2 type lymphocytes, with production of anti-inflammatory cytokines. In conclusion, the evidences gathered until now should be taken into consideration for future studies aiming to explore the possible role of H. pylori infection on human reproduction.